Overview of prescription errors involving duplicate active ingredients or contraindicated drugs for patients - Phan , Nguyễn Phương Thảo; Vo , Hoàng Vinh; Truong , Thị Xuân Thảo; Vo , Kiến Tài; Nguyen , Huy Hoàng (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Medication errors (ME) are preventable mistakes caused by the inappropriate use of medications that can harm patients. This is a significant patient safety issue and occurs frequently around the world. ME can happen at any stage of the prescribing, dispensing, and use of medications. Among these, prescribing errors (PE) are mistakes related to the selection of medications, such as incorrect indications, contraindications, allergy history, contraindications with ongoing treatments, and other factors. These errors can lead to increased side effects, reduced treatment efficacy, prolonged treatment duration, and higher healthcare costs for patients. Such incidents are associated with pressure on healthcare services and significant healthcare costs. To mitigate issues related to medication use, we need to implement several measures, such as regularly updating medication information, providing guidance on medication use to healthcare staff, and conducting counseling and monitoring of prescriptions and medication use.